Development of a Culture-Based Religious Humanistic Value Education Model at PTKIN Banda Aceh - Fakhrurrazi Fakhrurrazi; Legiman Legiman; M. Fadli; Tajuddin Al Alusi (Institut Agama Islam An-Nawawi Purworejo, 2023)
This research aims to find a culture-based model of humanist-religious values ​​education at PTKIN Banda Aceh, to find the development of a culture-based humanist-religious values ​​education model at PTKIN Banda Aceh and to find out the development of positive attitudes in humanist-religious education at PTKIN Banda Aceh. Based on the problem formulation and research objectives, this research seeks to find out, describe and reveal a phenomenon in the development of a culture-based religious humanistic value education model at the Faculty of Tarbiyah and Teacher Training (FTIK) UIN Arraniry Banda Aceh, as well as trying to reveal the facts that led to the implementation of activities whether it goes well or not, so that the phenomenon of the impact or consequences of these activities can be read through this study. This research method is qualitative descriptive research. Qualitative descriptive research is a research method that attempts to describe and interpret objects according to what they are. The source of data collection for this research is observation, interviews and documentation. The results of this research are that lecturers provide a model of respect for students and do not adopt an authoritarian attitude towards students. Authoritarian attitudes can damage humanistic values ​​with an Islamic religious culture, lecturers are proactive in encouraging students at the Faculty of Tarbiyah and Teacher Training (FTIK) UIN Arraniry, in developing models of humanistic value education for students who are currently studying at the Faculty of Tarbiyah and Teacher Training (FTIK). UIN Arraniry and religious culture in higher education are highly recommended to be developed by lecturers and students regarding humanistic values ​​education.